A co-prime array ultrasonic wind measurement method based on FL-ESB algorithm - Shan, Zebiao; Xie, Shijuan; Yu, Boli; Liu, Xiaosong (Measurement science & technology, 2025)
Accurate wind speed and direction measurement is crucial in many environmental applications, but achieving reliable results in the presence of mixed noise, such as impulse and Gaussian noise, remains a significant challenge. Traditional methods often fail to maintain accuracy under these conditions. This paper proposes a co-prime array wind measurement method based on fractional low-order eigenspace beam forming (FL-ESB) algorithm. The proposed method adopts a co-prime arc ultrasonic sensor structure consisting of two sets of uniform arc subarrays. This structure can increase the array aperture and improve the measurement accuracy. Combined with the idea of fractional low order covariance, the FL-ESB algorithm is proposed to realize the effective suppression of impulse and Gaussian mixed noise. The estimated variance and wind parameters’ Cramer Rao Bound are obtained through theoretical analysis and simulation. Simulation results show that under a signal-to-noise ratio of −4 dB, the root mean square error of wind speed is less than 0.6 m s −1 , and the root mean square error of wind direction angle is less than 2 ∘ . These results confirm that the proposed method effectively measures wind speed and direction in mixed noise environments.In conclusion, the FL-ESB-based co-prime array method provides a robust solution for accurate wind measurement, offering improved noise suppression and accuracy compared to traditional methods.